Discrepancies in the diagnosis of methicillin resistant Staphylococcus aureus among different hospitals in Lahore, Pakistan - T, Romeeza; A, Nadeem; J, Nauman; A, Afia; R, Kunwal (IIUM Medical Journal Malaysia, 2009)
Introduction: Staphylococcus aureus is a pathogen causing a wide range of infections. It changes its genome under the selection pressure of antibiotics. Methicillin resistance is commonly determined by Kirby-Bauer disc diffusion method which has low sensitivity and specificity. Thus, anti PBP-2a latex agglutination test was used to confirm the identity of those labeled as MRSA. Materials and Methods: One hundred bacterial samples characterized as MRSA according to Kirby-Bauer diffusion method were collected from different hospitals in Lahore. Results: Biochemical characterization of these MRSA isolates revealed that only 64 (64%) were actually S. aureus while the other 36 isolates (36%) were coagulase negative staphylococci. Further serological characterization revealed that among the 64 isolates of S. aureus, 50 (78%) were MRSA while 14 (22%) were MSSA. Conclusion: Therefore, overall, 50% of the bacterial strains were misidentified as MRSA. Misdiagnosis of antibiotic resistance may lead to an inappropriate prescription of medicines to these patients.